PENERAPAN METODE BERCERITA BERBASIS GAMBAR SERI UNTUK MENINGKATKAN KEMAMPUAN DAYA PIKIR DAN MENDENGARKAN - Wiwit Murzian (UNIB Press, 2023)
The purpose of this study was to describe the application of the storytelling method through serial picture media to improve thinking and listening skills in Group B children at Pembina Tais State Kindergarten. Subject of this research are B1 for CAR group, B2 for experiment group and B3 for control group. This type of research uses a combination of Classroom Action Research (CAR) with quasi-experimental. The technic used in data collection is an observation sheet. Analyze of data use mean persentage and t test. The results of the classroom action research showed an increase in children's thinking ability and listening ability between cycles. The application of the storytelling method through serial picture media is effective in improving children's listening skills. The implication of this research is that teachers can try to apply the storytelling method through picture series media as a daily learning method, especially in early childhood learning group B. The results of this study show storytelling can increase in children's thinking ability and listening ability